1994
DOI: 10.1111/j.1540-8191.1994.tb00910.x
|View full text |Cite
|
Sign up to set email alerts
|

Malperfusion of the Thoracoabdominal Vasculature in Aortic Dissection

Abstract: Ischemic damage to vital organs supplied by the thoracoabdominal aorta greatly increases the overall risk of aortic dissection. Of 320 patients operated upon for aortic dissection since 1985, 33 (10.3%) underwent operations directed at the relief of malperfusion (15/158 acute type A; 9/18 acute type B; 4/78 chronic type A; 5/66 chronic type B). Organs affected were the kidneys in 32; the bowel in 20; and the spinal cord in 1, while critical lower extremity ischemia was present in 11 patients. In total, 64 vasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…44 Primary surgical aortic repair results in successful revascularization in the vast majority of patients with type B dissection; however, the presence of renal or mesenteric ischemia has been correlated with especially high surgical mortality rates of 70% and 87%, respectively. 24,43,45,46 For this reason, alternative surgical procedures have been explored to address organ ischemia specifically. In particular, surgical aortic fenestration has been shown to relieve malperfusion syndrome in 93% to 100% of cases, with an in-hospital mortality rate of 0% to 43%.…”
Section: Malperfusion Syndromementioning
confidence: 99%
“…44 Primary surgical aortic repair results in successful revascularization in the vast majority of patients with type B dissection; however, the presence of renal or mesenteric ischemia has been correlated with especially high surgical mortality rates of 70% and 87%, respectively. 24,43,45,46 For this reason, alternative surgical procedures have been explored to address organ ischemia specifically. In particular, surgical aortic fenestration has been shown to relieve malperfusion syndrome in 93% to 100% of cases, with an in-hospital mortality rate of 0% to 43%.…”
Section: Malperfusion Syndromementioning
confidence: 99%
“…, In the literature, the mortality in aortic dissection with malperfusion has been reported to be about 30%. 2,[9][10][11] In the present series, the operative mortality in the malperfusion group was 31.3%. That in the nomalperfusion group was ILl %, which was significantly lower than that in the malperfusion group and superior to that in other reports.P The brain was affected in 3-7% of aortic dissection patients, the spinal cord in 1-3%, the intestine in 1-6%, the kidney in 3-10%, and the lower extremities in 3-24%, in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Ischaemia involving the spinal, coeliac, mesenteric, and renal or lower extremity vessels occurs in approximately 10-30% of the patients with aortic dissection [15,16,17]. In 1988, Shimshak et al first reported relief of claudication following balloon angioplasty of the true lumen of the abdominal aorta [32].…”
Section: Percutaneous Relief Of Branch Vessel Ischaemiamentioning
confidence: 98%
“…Patients with organ ischaemia are often poor candidates for anaesthesia and surgery. Surgical procedures may be technically difficult and operative mortality reported in literature ranges between 25 and 51%, mortality being higher in patients with critical mesenteric or renal ischaemia [1,15,16,17]; thus, percutaneous measures for relief of such ischaemia can significantly improve the prognosis in these patients. Over the past decade, successful relief of such ischaemia using less invasive interventional radiological techniques has been reported with procedure related mortality ranging between 0 and 25% [5,6,7,8,9,10,19,20].…”
Section: Therapeutic Strategy and Treatment Optionsmentioning
confidence: 99%
See 1 more Smart Citation